2014
DOI: 10.3109/00207454.2014.945643
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary observations on MRI correlates of driving independence and performance in persons with heart failure

Abstract: Reduced structural brain integrity is associated with poorer reported and simulated driving in persons with heart failure. Larger prospective studies that employ on-road testing are needed to clarify brain changes and risk for unsafe driving in heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Additional mechanisms by which increased cerebral venous pressure may promote cognitive decline include decreases of cerebral blood flow, microhemorrhages (Ungvari et al 2018(Ungvari et al , 2017b, and altered cerebrospinal fluid absorption (Fulop et al 2019). Heart failure patients are also frequently diagnosed with white matter hyperintensities (WMHs, a radiological finding showing damage in the white matter regions of the brain near the lateral ventricles on T2/ FLAIR MRI sequences) (Alosco et al 2013), which predict poorer attention and executive function (Alosco et al 2015). In addition to tissue ischemia (Makedonov et al 2013), increased cerebral venous pressure has been causally linked to the pathogenesis of WMHs (Fulop et al 2019;Moody et al 1995;Chung and Hu 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Additional mechanisms by which increased cerebral venous pressure may promote cognitive decline include decreases of cerebral blood flow, microhemorrhages (Ungvari et al 2018(Ungvari et al , 2017b, and altered cerebrospinal fluid absorption (Fulop et al 2019). Heart failure patients are also frequently diagnosed with white matter hyperintensities (WMHs, a radiological finding showing damage in the white matter regions of the brain near the lateral ventricles on T2/ FLAIR MRI sequences) (Alosco et al 2013), which predict poorer attention and executive function (Alosco et al 2015). In addition to tissue ischemia (Makedonov et al 2013), increased cerebral venous pressure has been causally linked to the pathogenesis of WMHs (Fulop et al 2019;Moody et al 1995;Chung and Hu 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Across three driving simulator studies, Alosco and colleagues (2013, 2015a, 2015b) found that older adults with heart failure (n = 18) had (1) poorer performance on attention/executive function tests and simulated driving compared to younger adults [35], (2) more WMH and reduced whole brain volume were associated with poor driving performance [36] and (3) decreased physical fitness was associated with poor driving performance [37]. During the simulation scenarios, collisions and missed stop signs were consistent markers of impaired driving performance.…”
Section: Heart Failurementioning
confidence: 99%
“…Poor simulated driving performance in HF has been theorized to largely involve the negative impact of cardiac dysfunction on the brain and subsequent cognitive dysfunction [4,5]. In particular, cognitive impairment in domains important for safe driving (e.g., attention/executive function) is prevalent in HF [4,6] and is correlated with poorer driving simulation performance in this population [3].…”
Section: Introductionmentioning
confidence: 99%
“…The associations among depressive symptoms, cognitive function, and objectively measured driving abilities in persons with HF is unclear. We sought to expand upon previous work from our group [3,5] and examine the relationship between depressive symptoms and driving simulation performance in older adults with HF. We hypothesized that greater depressive symptoms would negatively impact driving simulation performance, and cognitive dysfunction may offer one possible explanation for this phenomenon.…”
Section: Introductionmentioning
confidence: 99%